The Leiden/Argentine/Bonn (LAB) survey of Galactic HI : Final data release of the combined IDS and IAR surveys with improved stray-radiation corrections - Kalberla, P. M. W. (2005)
We present the final data release of observations of λ21-cm emission from Galactic neutral hydrogen over the entire sky, merging the Leiden/Dwingeloo Survey (LDS: Hartmann & Burton 1997, Atlas of Galactic Neutral Hydrogen) of the sky north of δ = -30° with the Instituto Argentino de Radioastronomía Survey (IAR: Arnal et al. 2000, A&AS, 142, 35; and Bajaja et al. 2005, A&A, 440, 767) of the sky south of δ= -25°. The angular resolution of the combined material is HPBW ∼ 0°.6. The LSR velocity coverage spans the interval -450 km s-1 to +400 km s-1, at a resolution of 1.3 km s-1. The data were corrected for stray radiation at the Institute for Radioastronomy of the University of Bonn, refining the original correction applied to the LDS. The rms brightness-temperature noise of the merged database is 0.07-0.09 K. Residual errors in the profile wings due to defects in the correction for stray radiation are for most of the data below a level of 20-40 mK. It would be necessary to construct a telescope with a main beam efficiency of ηMB ≳ 99% to achieve the same accuracy. The merged and refined material entering the LAB Survey of Galactic H I is intended to be a general resource useful to a wide range of studies of the physical and structural characteristices of the Galactic interstellar environment. The LAB Survey is the most sensitive Milky Way H I survey to date, with the most extensive coverage both spatially and kinematically.